1989
DOI: 10.1007/bf01313886
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of caprine, human and bovine strains of respiratory syncytial virus

Abstract: A new continuous ovine kidney cell line allowing the growth of caprine, human and bovine respiratory syncytial virus was used to minimize host cell related variations for the direct comparison of the viral ultrastructures, serological relationships and structural protein profiles. Results show that all three strains are closely related although a closer relationship was found between bovine and caprine RS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
3

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
15
0
3
Order By: Relevance
“…By electron microscopy, the morphology of the RSV virions appears to be either very pleomorphic, with a shape roughly rounded and a diameter between 150 and 35 nm, or filamentous with a length that can reach 5 µm and a diameter between 60 and 100 nm [147]. Regardless of the structure, each infectious particle contains a single functional copy of the genome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By electron microscopy, the morphology of the RSV virions appears to be either very pleomorphic, with a shape roughly rounded and a diameter between 150 and 35 nm, or filamentous with a length that can reach 5 µm and a diameter between 60 and 100 nm [147]. Regardless of the structure, each infectious particle contains a single functional copy of the genome.…”
Section: Introductionmentioning
confidence: 99%
“…Other pneumoviruses include pneumonia virus of mice (PVM), ovine (O)RSV and caprine (C)RSV. Although the RS viruses are structurally and antigenically related, BRSV and CRSV are the most closely related [2, 82,123,147].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several analyses on the molecular organization of the bovine RS viruses have been performed using human and bovine antisera, monoclonal antibodies (MAbs) and eDNA probes. They showed that the protein compositions of human and bovine RS viruses are very similar, with only minor differences in Mr between corresponding proteins (Cash et al, 1977;Lerch et al, 1989;Trudel et al, 1989). Electrophoretic mobilities of mRNAs of human and bovine RS viruses are comparable (Lerch et al, 1989).…”
mentioning
confidence: 99%
“…The comparison of the F protein sequence between these two human subtypes shows 89% overall homology (Johnson & Collins, 1988), consistent with the previously described high degree of antigenic relatedness. Information derived from electrophoretic analysis, immunoprecipitation and immunoblotting, have clearly established that the F proteins of both human and bovine RS virus strains present comparable structural characteristics (Kennedy et al, 1988;Trudel et al, 1989;Lerch et al, 1989) and antigenic relatedness (Taylor et al, 1984;0rvell et al, 1987;Lerch et al, 1989). To provide a molecular basis for these results, we present here the nucleotide and deduced amino acid sequences for the F protein of bovine RS virus strain RB 94 and compare them with human RS virus F sequence data (A and B subtypes).…”
mentioning
confidence: 99%
“…Although BRSV and HRSV are antigenically related, they differ in their pattern of reactivity with monoclonal antibodies (Mufson et al, 1985;()rvell et al, 1987;Beeler & van Wyke Coelingh, 1989). It has been shown that like that of HRSV, the genome of BRSV encodes 10 mRNAs (Lerch et al, 1989), and that the protein composition of these viruses is very similar, with only minor differences in Mr between corresponding proteins (Cash et al, 1977;Lerch et al, 1989;Trudel et al, 1989;Mallipeddi et al, 1990). To delineate the genetic basis for the differences between HRSV and BRSV, we and others have undertaken cDNA cloning and nucleotide sequencing of BRSV genes for comparison with the sequences of the genes of HRSV.…”
mentioning
confidence: 99%